(untitled) (New York, 2000)
This text is a study companion to "Molecular Cell Biology: 4th edition with CD-ROM", and is divided into three parts: reviewing concepts; analyzing experiments; and solutions to problems.
Keywords: Molecular biology,Sinh học phân tử